Entangled political economy - Koppl, Roger, 1957-; Horwitz, Steven (Emerald, 2014)
The term the "Entangled political economy" was first coined by economist Richard E. Wagner of George Mason University who challenged the "additive" political economy paradigm with his "entangled political economy," which sees public and private entities as equal and entwined players in exchange relations. This volume examines entangled political economy from several distinct but complementary points of view. The history of entangled political economy is traced to Adam Smith and Carl Menger and its implications are worked out for both theoretical and applied economics. New directions in economic modeling are struck. Finally, entanglement is found to imply complexity, which leads not only to somewhat non-standard mathematical methods in economics, but also principled limits to the explanatory and predictive power of mathematical models in political economy. The volume demonstrates that Wagners notion of entanglement opens new vistas for political economy in all its dimensions.
Keywords: Economics.; elektronické knihy; electronic books